An update on posterior-approach blepharoptosis surgery: Influence of clinical factors on surgical outcomes - Izabela Nowak-Gospodarowicz; Michał Kinasz; Aleksandra Kinga Kicińska; Marek Rękas (PLoS ONE, 2026)
Purpose To assess how preoperative clinical factors influence surgical outcomes following posterior-approach blepharoptosis repair. Design Prospective cohort study. Methods We conducted a prospective analysis of patients undergoing posterior-approach ptosis repair from 2022 to 2024. The primary outcome was change in marginal reflex distance 1 (ΔMRD1) at a 3-month follow-up. Secondary outcomes included inter-eye symmetry, contour, patient satisfaction (graded 0–2), surgery duration, and complication rates. We analyzed outcomes across three clinical subgroups: degree of ptosis (MRD1 ≥ 1 mm vs < 1 mm), levator function (LF > 8 mm vs 4–8 mm), and phenylephrine test result (positive vs negative). Results A total of 231 eyes were included. Mean MRD1 improved significantly from 0.14 ± 1.5 mm preoperatively to 4.0 ± 0.8 mm postoperatively (P < 0.001). Subgroup analysis showed that patients with greater preoperative ptosis (MRD1 < 1 mm) required more extensive surgery, but clinical outcomes and patient satisfaction did not differ significantly between groups. Neither levator function nor phenylephrine test results influenced final surgical success or patient satisfaction, but preoperative ptosis severity and phenylephrine test results impacted ΔMRD1. Conclusions Preoperative factors such as ptosis severity, levator function, and phenylephrine test result influence surgical planning but do not affect the final outcomes of posterior-approach blepharoptosis surgery. This evidence supports broader application of minimally invasive posterior approaches in clinical practice.